2012
DOI: 10.1139/y11-101
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the differential reduction of omega-3 and omega-6 highly unsaturated fatty acids by structural heart disease resulting in “HUFA deficiency”

Abstract: The causes of reduced levels of omega-3 and omega-6 highly unsaturated fatty acids ("HUFA deficiency") in heart failure remain unresolved. HUFA profiles were examined in the serum of 331 patients with failing versus nonfailing heart disease. Arachidonic acid was positively correlated (P < 0.001) with eicosapentaenoic acid (EPA) (r = 0.40) and docosahexaenoic acid (DHA) (r = 0.53) and negatively with palmitic (r = 0.42), palmitoleic (r = 0.38), and oleic acid (r = 0.48). Delta-5 desaturase activity was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 62 publications
1
26
2
4
Order By: Relevance
“…Омега-3 индекс эритроцитов периферической крови, отражающий содержание омега-3 ПНЖК в кардио-миоцитах, рассматривается как фактор прогноза сер-дечно-сосудистых событий [5,6]. Исследованиями последних лет установлено, что прогностическое зна-чение имеет не только содержание в крови омега-3, но и омега-6 ПНЖК [4,[7][8][9]. Вопросы изучения дина-мики ПНЖК при декомпенсации ХСН, а также на фоне ее лечения, остаются мало освещенными.…”
Section: Methodsunclassified
“…Омега-3 индекс эритроцитов периферической крови, отражающий содержание омега-3 ПНЖК в кардио-миоцитах, рассматривается как фактор прогноза сер-дечно-сосудистых событий [5,6]. Исследованиями последних лет установлено, что прогностическое зна-чение имеет не только содержание в крови омега-3, но и омега-6 ПНЖК [4,[7][8][9]. Вопросы изучения дина-мики ПНЖК при декомпенсации ХСН, а также на фоне ее лечения, остаются мало освещенными.…”
Section: Methodsunclassified
“…A high availability of fatty acids in an obese state is associated with increased fatty acid utilisation. However, in view of the finding that an increased fatty acid oxidation arising from fenofibrate treatment of young rats increased 20:4n-6 but not 22:6n-3 (Rupp et al 2012), involvement of other parameters has to be inferred. Because it is well documented that increased abdominal fat is associated with a raised sympathetic activity (Canale et al 2013;Rupp and Maisch 2003) and it was previously shown that a hypercaloric intake was associated with an increased heart rate (Rupp and Maisch 1999), it was examined Standardized ␤-coefficients were given for significant differences.…”
Section: Relation Of Dha To Abdominal Fat Mass and Beta-oxidationmentioning
confidence: 99%
“…For safety reasons, hydrogen was used as carrier gas produced by an H2-50XR Hydrogen Generator (SRI Instruments, Torrance, California, USA). Extraction of triacylglycerols and phospholipids and fatty acid transesterification to methyl esters were done as previously described (Rupp et al 2006(Rupp et al , 2012 (Michaud et al 2002) was performed. As internal standard, C17:0 methyl heptadecanoate was used (Dr. Ehrenstorfer GmbH, Augsburg, Germany).…”
Section: Fatty Acid Analysis Using Gas Chromatographymentioning
confidence: 99%
See 2 more Smart Citations